Pre-conditioning with IFN-γ and hypoxia enhances the angiogenic potential of iPSC-Derived MSC secretome - Wang, Suya (2022)
Induced pluripotent stem cell (iPSC) derived mesenchymal stem cells (iMSCs) represent a promising source of progenitor cells for approaches in the field of bone regeneration. Bone formation is a multi-step process in which osteogenesis and angiogenesis are both involved. Many reports show that the secretome of mesenchymal stromal stem cells (MSCs) influences the microenvironment upon injury, promoting cytoprotection, angiogenesis, and tissue repair of the damaged area. However, the effects of iPSC-derived MSCs secretome on angiogenesis have seldom been investigated. In the present study, the angiogenic properties of IFN-γ pre-conditioned iMSC secretomes were analyzed. We detected a higher expression of the pro-angiogenic genes and proteins of iMSCs and their secretome under IFN-γ and hypoxic stimulation (IFN-H). Tube formation and wound healing assays revealed a higher angiogenic potential of HUVECs in the presence of IFN-γ conditioned iMSC secretome. Sprouting assays demonstrated that within Coll/HA scaffolds, HUVECs spheroids formed significantly more and longer sprouts in the presence of IFN-γ conditioned iMSC secretome. Through gene expression analyses, pro-angiogenic genes (FLT-1, KDR, MET, TIMP-1, HIF-1α, IL-8, and VCAM-1) in HUVECs showed a significant up-regulation and down-regulation of two anti-angiogenic genes (TIMP-4 and IGFBP-1) compared to the data obtained in the other groups. Our results demonstrate that the iMSC secretome, pre-conditioned under inflammatory and hypoxic conditions, induced the highest angiogenic properties of HUVECs. We conclude that pre-activated iMSCs enhance their efficacy and represent a suitable cell source for collagen/hydroxyapatite with angiogenic properties.